Generating Aerosols - Brian H. Kaye (KONA Powder and Particle Journal, 2014)
The generation of aerosols has always been an important concern in studies of the hazards of inhaled materials. In recent years the need to generate aerosols for test purposes has spread into many areas of technological endeavour. Literature dealing with the problems associated with the various techniques of aerosol generation has spread into a diversity of technical areas and the relevant literature is not always easy to retrieve, especially since the term "Aerosol Generation" rarely appears in the title of an article. For example, a study of the use of a diffractometer based method of measuring a size distribution would not state that efficient generation of aerosols is a major concern in the accuracy of the data. In this review article, the diverse literature is focused to facilitate the retrieval of appropriate information for scientists who must generate aerosols as part of a larger investigation.